Hukum Islam di Persimpangan: Menjawab Tantangan Bioetika dan Kecerdasan Artifisial - Bobby Ferly; Salma Salma; Muchlis Bahar (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
Islamic law faces significant challenges from the rapid advancements in bioethics and artificial intelligence (AI). The current responsive approach, based on ad-hoc fatwas, is deemed inadequate to address the systemic ethical dilemmas posed by these disruptive technologies. This research aims to propose a proactive and systematic ijtihad framework capable of anticipating and guiding technological innovation to align with the higher objectives of Shari'ah (Maqasid al-Shari'ah). Using a qualitative, library-based method with a juridical-normative and philosophical approach, this study analyzes primary and secondary Islamic legal sources through the Maqasid al-Shari'ah theoretical framework. The research finds the current model to be limited and, as a solution, offers a novelty in the form of the Hierarchical Model of Technological Ijtihad (HI-Tech). This model is a structured, interdisciplinary reasoning process, supported by a proposed institution, the Bio-Artificial Ijtihad Council (MIBA), and a digital platform, "Nur-Fatwa," for dissemination. The implication of these findings is the need for a paradigm shift for Islamic legal institutions towards an anticipatory, interdisciplinary, and institutionalized approach to address contemporary technological issues, thereby ensuring the continued relevance of Islamic law.